2019
DOI: 10.33751/pedagog.v3i1.982
|View full text |Cite
|
Sign up to set email alerts
|

Speed Reading: University Efl Students� Strategies and Perceptions

Abstract: EFL reading classes are often teacher-centered and only focus on direct knowledge transmission, the emphasis is often put on the production of comprehension rather than the processing skills. This research attempts to maximize the students participation in evaluating the process of reading by using speed reading program, to find out the strategies they use in the reading process, and to know the students perceptions on speed reading in order to enhance their reading comprehension skill in English. The particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…Nevertheless, the result of this study is consistent with the result of other researchers, particularly in this field (Arab, 2009;Armagan & Genc, 2017;Chang, 2010;Chung & Nation, 2006;Hidayati, 2019;Yunus, 2016;Rasinski & Young, 2015;Ur, 2012). In almost a similar trace, Armagan and Genc (2017) 's study found that Turkish EFL students in the experimental group improved their reading rate from an average of 136.38 wpm in the pretest to 196.73 wpm in the posttest.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Nevertheless, the result of this study is consistent with the result of other researchers, particularly in this field (Arab, 2009;Armagan & Genc, 2017;Chang, 2010;Chung & Nation, 2006;Hidayati, 2019;Yunus, 2016;Rasinski & Young, 2015;Ur, 2012). In almost a similar trace, Armagan and Genc (2017) 's study found that Turkish EFL students in the experimental group improved their reading rate from an average of 136.38 wpm in the pretest to 196.73 wpm in the posttest.…”
Section: Discussionsupporting
confidence: 92%
“…The participants scored an average of 57.6% on the first test but changed to a better result on the posttest, 72.4%. This improvement is in line with Hidayati's (2019) study, in which participants scored 58.33% in speed reading test in the first and 84.52% in the last. Hidayati (2019) stated that this improvement made 21 participants more motivated and they could evaluate their own weak points in reading.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…EFL learners' ability to read and comprehend materials written in English is very important. It is one of the requirements to succeed in academic life and their profession after completing their study (Hidayati, 2019). She went on to say that speed reading should become a significant concern in the development of English teaching in Indonesia to prepare graduates to be efficient readers.…”
Section: The Implication Of Speed Reading For Indonesian Efl Learners...mentioning
confidence: 99%